PARTISIPASI MASYARAKAT DALAM PENGAWASAN DILIHAT DARI KETERWAKILAN PEREMPUAN PADA PEMBANGUNAN POLITIK DI PROVINSI KEPULAUAN RIAU - Maryanti Maryanti (Jurnal Bawaslu Provinsi Kepulauan Riau, 2020)
This paper aims to analyze society participation in supervision as seen from women's representation in political development in Riau Islands Province. Despite various efforts, women's participation and representation in politics are still low. Riau Islands Province is one of the provinces in Indonesia wherewomen's representation in legislative institutions is low compared to other provinces. The research method used is to conduct a literature study about society participation and representation of women. In this study it was found that there were various problems in the low participation of women. On the other hand, this study also found that there are opportunities for society participation and women's representation. The regional government is one of the actors that can issue regional regulations to make sure gender mainstreaming in the region. At the end of the study, the authors gave several recommendations to stakeholders on society participation in overseeing women's representation in political development in the Riau Islands Province.